Percussion Instruments Tuned - Jane Beethoven; Rosanne Emery; Cliff Lenz.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1991)
Viewers see and hear tuned percussion instruments from different parts of the world - - Compare tuned percussion instruments from Zimbabwe, Trinidad and Tobago, Vietnam and Indonesia - - Hear a variety of sounds produced by instruments constructed from an assortment of materials - - See an 8 year old student play Bach on the marimba, and jazz on the vibraphone.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - For Discussion - - General Information - - Correlations with THE MUSIC CONNECTION - - Student Follow-up - - Vocabulary - - About the Library.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: Percussion instruments; Musical instruments; Films for the hearing impaired